The Influence of Social Sciences Teachers in Overcoming Forgetting and Learning Boredom on Students' Learning Achievement in Grade X of SMA Negeri 1 Panyabungan Utara - Husein NST, Ahmad; Ansari, Rajab (PT Inovasi Pratama Internasional, 2025)
The formulation of the research problem is